Evaluasi Efektivitas Program Intervensi Ketahanan Keluarga Anti Narkoba yang dilakukan oleh Badan Narkotika Nasional Kota Tanjungpinang dalam Mencegah Penyalahgunaan Narkoba - Endri Endri; Riskio Riskio (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Drug abuse is a serious problem in Indonesia, including in Tanjungpinang City. The family has an important role in drug prevention. Tanjungpinang BNNK implements a family resilience intervention program to increase the role of families in drug prevention. This journal aims to determine the effectiveness of the Tanjungpinang National Narcotics Agency Anti-Drug Family Resilience Intervention Program in increasing family knowledge, attitudes and behavior towards drug abuse.